The Influence of Organizational Culture and Work Motivation on the Performance of MSME Actors in the Tda Bekasi Community - Salvarisi, Shabina Ajeng; Irawan, Pristanto Ria; Saputra, Allyya (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Study This aim For analyze influence culture organization and motivation Work to performance MSME actors in the Bekasi Hands Up Community (TDA). MSMEs have role important in Indonesia's economy , however Still face various challenge in increase performance they . Study This use approach quantitative with method survey towards 95 MSME actors who joined in Bekasi TDA Community . Data is collected through questionnaire and analyzed use method analysis regression multiple . Research result show that culture organization and motivation Work own influence positive and significant to performance MSME actors . Culture strong and adaptive organization in the TDA Bekasi community is proven capable increase performance its members . Temporary that 's motivation high work also contributes to the increase productivity and efficiency MSME actors . Study This give implications important for MSME development , in particular in context community business , as well highlighting importance build culture supporting and enhancing organizations motivation work of MSME actors.